Keberkesanan audiasi ke atas prestasi pendengaran muzik dan keupayaan menulis melodi secara kreatif dalam kalangan pelajar sekolah menengah rendah / Liow Bee Teen - Liow , Bee Teen (2021)
This study aims to examine the effectiveness of Audiation. Literature references indicate that there are scholars who suggest that the use of Audiation can be used to enhance students' listening ability, singing skills and creativity in writing melodies. Therefore, the objective of this study is for researchers the effect of Audiation on the ability to listen to music in terms of tonality and rhythm, singing skills in terms of rhythm, pitch and melody and creativity of students' melody writing in terms of originality, fluency and elaboration. The study sample consisted of 90, 14-year-old students studying in Tanjong Malim, Perak. This study employed pre-test design and post-test treatment group who underwent an intervention with Audiation. The duration of treatment was 90 minutes per week for ten weeks and all study subjects completed all assignments in pre- and post-intervention. The Music Aptitude Profile measurement instrument created by Edwin Gordon was used to collect data for this study. The results of the multivariate test, the SPANOVA test, show that the level of achievement of students after exposure to the use of Audiation in deep listening, singing and creative melody writing and the resulting profile plot is positive and successful. In addition the results of the study also show that there are significant relationship between the level of listening to music and Audiation; singing skills significantly affect singing quality (pic, rhythm and melody). Besides that, Audition has a positive effect on the creativity of creating melodies among students. The results show that Audiation has a positive effect on students' ability to listen to music, singing skills and creativity in writing melodies. The findings of this study confirm that the implementation of Audiation in music teaching in the classroom can improve the performance and achievement of better- quality music in terms of pitch singing, accuracy of rhythm applause, performance and melody writing as well as appreciation of music art for life. Recommendations for future studies include researching the use of Audiation extended to the upper secondary school level with the extension of skills in improvisation of students' melody writing.